2020
DOI: 10.14740/cr972
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation: Insight Into the Intimate Mechanisms of Coagulation

Abstract: Background: Atrial fibrillation (AF) is a hypercoagulable state. However, the intimate mechanisms leading to impaired coagulation and the timing of their activation are unclear. The aim of the study was to investigate the factors that initiate the coagulation cascade in the early hours (up to 48 h) of clinical manifestation of paroxysmal atrial fibrillation (PAF).Methods: Tissue factor (TF) level, coagulation activity of factor VII (FVIIa), factor XII (FXIIa) and factor XI (FXIa) were measured in plasma of 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Studies here are also controversial [25][26][27]. Our results showed significant activation of coagulation [14][15][16][17]. The statistical analysis showed no significant difference between the patient and the control group in terms of age and sex demographics, as well as in accompanying diseases and treatment, deleterious habits and BMI (p> 0.05) (Table 4).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Studies here are also controversial [25][26][27]. Our results showed significant activation of coagulation [14][15][16][17]. The statistical analysis showed no significant difference between the patient and the control group in terms of age and sex demographics, as well as in accompanying diseases and treatment, deleterious habits and BMI (p> 0.05) (Table 4).…”
Section: Discussionmentioning
confidence: 57%
“…At the same time, this could complement and expand the established embolic risk assessment scale for AFthe CHA2DS2-VASc score. Our previous studies showed that the clinical manifestation of PAF is associated with very early activation of the coagulation process [14][15][16][17]. We found that as early as the first twenty-four hours of the disease there was a significant increase in plasma coagulation activity of factor II (FII, p <0.001), factor V (FV, p <0.001), factor VII (FVII, p <0.001), factor FVIII (FVIII, p <0.001), factor IX (FIX, p <0.001), factor X (FX, p <0.001), factor XI (FXI, p <0.001), factor XII (FXII, p <0.001), vWF activity (p <0.001), as well as plasma levels of tissue factor (TF, p <0.001), FVIII (p <0.05), vWF (p <0.001), prothrombin fragment 1+2 (F1 + 2, p <0.001) and fibrinopeptide A (FPA, p <0.001) in the studied patient population, compared to controls without prior arrhythmic data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AF is a hypercoagulable state. Through bioinformatics analysis in the previous stage, compared with the CON group, HBG1 and HBD were significantly increased in the AF group, while HBG1 and HBD were the main molecules involved in oxygen transport, and HBG1 and HBD had a significant protein interaction with factor Xa, resulting in a significant difference in coagulation function between the AF group and the CON group; Mariya Negreva et al found that paroxysmal AF tends to have an early hypercoagulable state, involving intrinsic and extrinsic coagulation pathways in their study (Negreva et al, 2020). Rivaroxaban is a commonly used clinical anticoagulant.…”
Section: Discussionmentioning
confidence: 84%
“…Тому виникнення розладів кровотоку в лівому передсерді підвищує ризик серцево-емболічних подій з утворенням тромбу та зміною показників гомеостазу із залученням внутрішніх і зовнішніх шляхів коагуляції. Доведено, що в пацієнтів із ФП спостерігається підвищений рівень показників коагуляційної активності, таких як D-димер, фібриноген, антитромбін III (ATIII), комплекс тромбін-антитромбін III, фрагментів протромбіну, що сприяє посиленню гемокоагуляції [18][19][20]. Небезпека ФП для пацієнта пов'язана з виникненням серйозних ускладнень: порушенням гемодинаміки з розвитком серцевої недостатності та тромбоемболій.…”
Section: вступunclassified